1986
DOI: 10.1111/j.2042-3306.1986.tb03600.x
|View full text |Cite
|
Sign up to set email alerts
|

Ground reaction force patterns of Dutch Warmblood horses at normal walk

Abstract: Summary The ground reaction force patterns from 20 clinically sound Dutch Warmblood horses (Group A) were recorded at the normal walk. The data from four to 10 stance phases of each limb were computer averaged after normalisation to the animal's body mass and to the stance time. This analysis method allowed comparison of data from left and right fore‐ and hind‐limbs within and between horses. The left‐to‐right symmetry in the reaction force peaks of contralateral limbs of one horse exceeded 90 per cent. The ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
162
2
6

Year Published

1986
1986
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 179 publications
(191 citation statements)
references
References 9 publications
21
162
2
6
Order By: Relevance
“…One difficulty of force plate studies is the inability to control where the animal places its feet on the ground (Barrey, 1999). Merkens et al (1985) reported that multiple attempts (average 2.9) were needed to provide adequate data on the force exerted by a single limb of a horse, and Corr et al (2003), testing broiler chickens, required on average 10 attempts per bird before sufficient data had been collected. This creates challenges for researchers in terms of keeping animals walking and avoiding fatigue.…”
Section: Technical Issuesmentioning
confidence: 99%
“…One difficulty of force plate studies is the inability to control where the animal places its feet on the ground (Barrey, 1999). Merkens et al (1985) reported that multiple attempts (average 2.9) were needed to provide adequate data on the force exerted by a single limb of a horse, and Corr et al (2003), testing broiler chickens, required on average 10 attempts per bird before sufficient data had been collected. This creates challenges for researchers in terms of keeping animals walking and avoiding fatigue.…”
Section: Technical Issuesmentioning
confidence: 99%
“…A well-trained chnically sound horse at normal walk demonstrates a remarkable reproducibility in walking velocity and shape of the force plate signals [9]. Furthermore, no correlation was found between signal amplitude, being merely determined by F z, and the walking velocity and stance phase duration, all determined in the range where the animals walked at their own preferred, comfortable speed.…”
Section: Discussionmentioning
confidence: 88%
“…As shown in another paper [9], the resemblance between tracings of one horse over several years is greater than that between the horse under study and the 'standard horse'. Therefore, comparison with former tracings is preferred over the next best alternative, comparison with the 'standard horse'.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations